2005
DOI: 10.1103/physrevb.71.144203
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and inelastic deformations of ethylene-passivated tenfold decagonalAlNiCoquasicrystal surfaces

Abstract: The adhesion and friction force properties between a tenfold Al-Ni-Co decagonal quasicrystal and a titanium nitride (TiN)-coated tip were investigated using an atomic force microscope in ultrahigh vacuum. To suppress the strong chemical adhesion found in the clean quasicrystal surfaces, the sample was exposed to ethylene that formed a protective passivating layer. We show that the deformation mechanism of the tip-substrate junction changes from elastic to inelastic at a threshold pressure of 3.8 to 4.0 GPa. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Apart from the intrinsic aperiodic structure and the well known unusual physical bulk properties, 1 QC possess many interesting surface features such as good oxidation resistance compared to pure Al single crystals and a particularly low coefficient of friction. [2][3][4][5][6][7] In the research of surface properties and their relation to the aperiodic structure the twofold surfaces of the d-Al-Ni-Co quasicrystal are of special interest since they allow a simultaneous investigation of a periodic and perpendicular to it an aperiodic axis on same surface. An outstanding example for a simultaneous measurement of surface physical properties directly related to this two inequivalent surface directions of the clean ͑10000͒ d-Al-Ni-Co surface is the friction anisotropy measurement of Park et al 6 They reported a 7.8 times lower friction coefficient along the aperiodic compared to the periodic axis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the intrinsic aperiodic structure and the well known unusual physical bulk properties, 1 QC possess many interesting surface features such as good oxidation resistance compared to pure Al single crystals and a particularly low coefficient of friction. [2][3][4][5][6][7] In the research of surface properties and their relation to the aperiodic structure the twofold surfaces of the d-Al-Ni-Co quasicrystal are of special interest since they allow a simultaneous investigation of a periodic and perpendicular to it an aperiodic axis on same surface. An outstanding example for a simultaneous measurement of surface physical properties directly related to this two inequivalent surface directions of the clean ͑10000͒ d-Al-Ni-Co surface is the friction anisotropy measurement of Park et al 6 They reported a 7.8 times lower friction coefficient along the aperiodic compared to the periodic axis.…”
Section: Introductionmentioning
confidence: 99%
“…Both groups have their advantages and can be used complementary to reveal quasicrystalline surface structures. The STM results presented here are therefore compared with the results of surface diffraction methods, [11][12][13] STM measurements of the ͑10000͒ surface, 4,14 and are compared in all three dimensions with an appropriated bulk atomic model of the investigated crystals. 15 The structure of the low-index surface ͑10000͒ d-Al-Ni-Co was investigated by STM by Kishida et al 14 and Park et al, 4 by helium atom scattering ͑HAS͒ and SPA-LEED ͑Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Friction is a complex phenomenon, with many channels contributing to energy dissipation. Park and co-workers used atomic force microscopy (AFM) and STM to study the twofold surface of d-Al-Ni-Co which contains both periodic and quasiperiodic directions [51,75,120]. By measuring the torsional response of the AFM cantilever, they could directly compare frictional effects along the periodic and aperiodic directions on the same surface.…”
Section: Wider Impactmentioning
confidence: 99%
“…At low temperatures, benzene (C 6 H 6 ) was found to adsorb in a disordered fashion on i-Al-Pd-Mn [74]. Ethylene (C 2 H 4 ) was used to passivate the tenfold surface of dAl-Ni-Co in measurements of the friction of the surface using atomic force microscopy [75].…”
Section: Adsorption and Growthmentioning
confidence: 99%